Varisela, Skabies, dan Pityriasis Versicolor pada Remaja yang Tinggal di Asrama - Sri Yulianti; Wizar Putri Mellaratna (Lembaga Pengembangan Kinerja Dosen, 2025)
Varicella is a contagious skin infection caused by the varicella zoster virus (VZV). Varicella, scabies, and pityriasis versicolor are diseases with the same risk factors, namely in adolescents with high physical activity and living in crowded places such as dormitories. Case: A 13-year-old male adolescent complained of fluid-filled bumps on the body and face accompanied by itching that had been felt since yesterday. Low fever that fluctuates accompanied by dizziness, nausea since 2 days ago. Due to the itching, the patient scratched the area of ​​the bumps so that the bumps burst. The patient is currently undergoing scabies treatment. The patient also complained of white spots all over the body that had appeared since 2 months ago and worsened when the patient sweated. The patient is a student living in an Islamic boarding school. The patient said he often changed clothes, sarongs, and caps with his dorm mates. The patient also has high physical activity such as playing ball and does not immediately change clothes if he sweats. The diagnosis of varicella, scabies, and pityriasis versicolor is based on anamnesis and physical examination. Treatment options in this case are administration of drugs in the form of Acyclovir 400mg 4 x 2, Paracetamol 500mg 3 x 1, Permethrin 5% applied to the entire body 1x for 8 hours, Fucilex cream 2 dd ue, and Ketoconazole 2% shampoo. Conclusion: in this case, a 13-year-old patient with varicella, scabies, and pityriasis versicolor with risk factors of adolescence with high physical activity and living in crowded places such as dormitories was found.